PENGETAHUAN STIKER 10 PESAN GIZI SEIMBANG TERHADAP STATUS GIZI DAN HIPERTENSI PADA SOPIR MINIBUS JURUSAN MANADO-GORONTALO DI REST AREA DESA BUSISINGO - Daniel Robert; Vera T. Harikedua; Stifly C. Tulung (POLTEKKES KEMENKES MANADO, 2016)
Balanced nutrition is the food consumed by everyday individuals who are diverse and meetthe five groups of nutrients in sufficient quantities, not excessive and not kekurangan.tujuanthis study was to determine the knowledge of 10 messages balanced nutrition on nutritionalstatus and hypertension in the minibus driver Manado-Gorontalo majors in the rest areaBusisingo village.The method used in the study was a descriptive study using observational design. Thepopulation in this study were all driver who crossed the road trans Sulawesi. The sample is adriver who still do activities as a driver who are 32 respondents. 10 data collection stickerknowledge of balanced nutrition messages using a questionnaire. The nutritional status bytaking anthropometric data, and blood pressure was measured by a sphygmomanometer.The results obtained by most survey respondents between the ages of 29-34 years. Afteranalyzing the data in a descriptive way the majority of respondents have knowledge aboutbalanced nutrition 10 messages classified as good by 26 respondents (81.2%) and 6respondents (18.7%) knowledge of 10 messages balanced nutrition moderate. Mostrespondents had a normal nutritional status by category with a percentage (56.2%). Bloodpressure checks as many as 32 samples, it was found that 14 respondents (43.7%) hadnormal blood pressure categories, and 18 respondents (56.2%) had mild hypertension bloodpressure categories.The conclusion of this study we can conclude that knowledge of balanced nutrition sticker 10messages on the driver minibus Manado-Gorontalo generally quite good, has a normalnutritional status and had a blood pressure with mild hypertension classification.